Teaching Video NeuroImage: Restless Abdomen: A Rare Variant of Restless Legs Syndrome. (17th May 2022) - Sun, Zhanfang; Tan, Yinyin; Li, Zhen; Yang, Liling; Sun, Xuedong; Du, Yifeng; Chen, Yan
Abstract : A 60-year-old man presented with difficulty falling asleep and unpleasant abdominal sensations for over 2 years. His medical history was unremarkable except for benign prostatic hyperplasia. He experienced unpleasant abdominal sensations 30 minutes after lying down, which partially improved after rubbing or slapping his abdomen and walking. He denied symptoms of heartburn or reflux. Hemoglobin, iron, and ferritin were normal. Gastrointestinal endoscopy and abdominal CT were normal. Video-polysomnography revealed an urge to move his abdomen during periods of rest and periodic limb movements of sleep (PLMS) (Video 1). A rare variant of restless legs syndrome (RLS), restless abdomen, was considered. e1 Most patients improve with dopaminergic treatment. 1, 2 The effectiveness of dopaminergic therapy for RLS, restless abdomen, and PLMS suggests that they may share a similar pathophysiology, although the exact mechanism remains unclear. e2, e3 Our patient has responded well to pramipexole (0.25 mg/d) for 8 months.